The impact of ACE inhibitors on the risk of SARS-CoV-2 virus infection and the course of COVID-19 disease - Plech, Tomasz (Polish Journal of Public Health, 2020)
Invasion of SARS-CoV-2 virus into human cells is mediated by the interaction of viral particles with a specific protein – angiotensin-converting enzyme 2 (ACE-2). Due to the involvement of ACE-2 in blood pressure regulation, there have appeared reports of possible negative effects of taking some cardiological drugs during coronavirus pandemic. Some hypotheses suggest an increased risk of SARS-CoV-2 infection and more severe clinical course of COVID-19 in patients treated with angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers. In the face of contradictory information regarding this question, several societies of cardiology and hypertension have issued clinical recommendations for patients treated with the above-mentioned drugs. These recommendations conclude that there are no unambiguous data that would support the hypothesis about the negative effects of angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers on patients infected with SARS-CoV-2 virus. Therefore, it is highly recommended not to discontinue treatment in patients in whom these drugs lead to improvement in their clinical condition. The impact of ACE inhibitors on the risk of SARS-CoV-2 virus infection and the course of COVID-19 disease.